Comparative analysis of dynamic and formal approaches to translation. - Padilla Veloz, Esmeralda Estefanía (2014)
This thesis is a result of a depth analysis comparing dynamic and formal approaches to translation as a science. Its importance arises from the panorama of Translation in a local field such as Guayaquil. There is so much empirical know-how that triggers the interrogation of how healthy is for a professional to work in the field without certain deep theoretical knowledge. This is the lead towards a more specific objective: to highlight and identify the strategies and multiple choices that translators from Spanish to English and vice versa possess at the moment of performing a translation. This document is strongly related to Eugene Nida’s concept of formal and dynamic equivalence in which we will go through to have a better understanding of the decision-making process and the importance of comparing both perspectives. Our goal is to provide further information and reasons to create a solid foundation for these types of decisions within the linguistic field. The study and research of this thesis is centered on past interviews, articles and opinions from the most successful pioneers of translators around the globe which, at the end, brings a conclusion in mixing both approaches.